A study for the development of a curriculum development model for nursing education - Louise de Villiers (AOSIS, 1998)
The process and main findings of a qualitative, interpretative-theoretical study aimed at designing a model for curriculum development in nursing and formulating criteria for a new nursing curriculum, are discussed. Opsomming Die proses en algemene bevindinge van 'n kwalitatiewe, interpretatief-teoretiese studio, wat die ontwerp van 'n model vir kurrikulumontwikkeling in verpleegkunde en formulering van kriteria vir 'n nuwe verpleegkundekurri- kulum ten doel gehad het. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.